Odontologia adesiva atual: uma revisão de literatura - Franco, Laura Molinar [UNESP]; Gonçalves, Rafael Simões [UNESP]; Pellizzer, Eduardo Piza [UNESP] (My University, 2013)
Over the decades, there was an evolution in dentistry, specifically in filling technique, and Buonocore (1955) has been the introducer of Adhesive Era. Thus, this paper aims to review the literature about the current adhesive systems. Was performed a literature review about the 5th and 6th adhesive system generations. The titles and abstracts of published articles were analyzed in PubMed database over the past 5 years. However, there are still different views about the technique used, therefore, because the diversity of these materials, it is impossible to highlight one that presents the best efficiency in all situations, being the responsibility of the professional the knowledge of the techniques and clinical applicability of each material.

Com o passar das décadas, houve uma evolução na odontologia, mais especificamente das técnicas restauradoras, sendo Buonocore (1955) o introdutor da Era Adesiva. Sendo assim, este trabalho tem como objetivo revisar a literatura acerca dos sistemas adesivos atuais. Foi realizada uma revisão de literatura sobre os sistemas de 5º e 6º gerações. Os resumos e títulos dos artigos publicados foram analisados na base de dados PubMed nos últimos 5 anos. No entanto, ainda há divergência de opiniões quanto a técnica empregada, sendo assim, diante da diversidade desses materiais, torna-se impossível destacar aquele que apresente melhor eficácia em todas as situações, sendo de responsabilidade do profissional obter o conhecimento das técnicas e da aplicabilidade clínica de cada material.
Current dental adhesive: a literature review
Keywords: Dental leakage; Adhesives; Acid etching, dental; Infiltração dentária; Adesivos; Condicionamento ácido dentário